PENGARUH COGNITIVE BEHAVIOUR THERAPY TERHADAP TINGKAT KECEMASAN PASIEN PRE OPERASI DI RUMAH SAKIT UMUM AL-FATAH AMBON - Nova Bugis; Davita S. Batoek (STIKES Pasapua Ambon, 2020)
Introduction: Surgical procedures will cause various kinds of emotional reactions for patients who will undergo them, one of the reactions that arises is anxiety. Non-pharmacological anxiety management cognitive behavior therapy can be used to reduce anxiety levels. The purpose of this study was to determine the effect of cognitive behavior therapy on the anxiety level of preoperative patients. Method: a pre-experimental design with the static group comparison approach: randomized control group only. The population is all preoperative patients at Al-Fatah Hospital in Ambon. Sampling using accidental sampling technique. The sample in this study was 30 people who were divided into 15 people for the group that was given cognitive behavior therapy (the intervention group) and 15 people for the group that was not given cognitive behavior therapy (the control group). Result: The results of the study were obtained from 30 respondents where the level of anxiety in preoperative patients at Al-Fatah Hospital Ambon in 2019, after being given cognitive behavior therapy in the intervention group, namely no anxiety on a scale of 0-13 (86.7%) and mild anxiety on a scale 14-20 (13.3%), whereas in the control group mild anxiety scale 14-20 (33.3%), moderate anxiety (46.7%) scale 21-28 (46.7%), and severe anxiety scale 28-41 (20.0%). From the results of data analysis using the t-independent statistical test, it was obtained that the value of p = 0.000 <0.05. Conclusion: that there is an effect of cognitive behavior therapy on the anxiety level of preoperative patients at Al-Fatah Hospital, Ambon. It is suggested to nurses to be able to use this non-pharmacological anxiety management to reduce the anxiety level of preoperative patients.